A thermodynamically consistent constitutive model for diffusion-assisted plasticity in Ni-based superalloys. (June 2018) - Barba, D.; Alabort, E.; Garcia-Gonzalez, D.; Moverare, J.J.; Reed, R.C.; Jérusalem, A.
Abstract: An elasto-viscoplastic thermodynamically consistent constitutive model for diffusion-assisted phase transformations is presented here. The model accounts for the different deformation mechanisms, their time dependence, the crystal rotations produced by microtwin propagation and the chemistry-plasticity coupling occurring at high temperature. It is applied to the study of the chemically assisted microtwinning observed in Ni-based superalloys in the temperature range of 600–800 °C. The model parameters are calibrated against multi-directional mechanical data from tensile creep tests of single crystal superalloy MD2. The constitutive model is then implemented into a crystal plasticity finite element code to study the activation of the different deformation mechanisms within single crystal and polycrystalline aggregates. Doing so, a relation between the rotations of the crystal and the creep life of the different crystal orientations is established. The results eventually reveal the critical role of the strong anisotropy of microtwin formation on the asymmetric behavior of the alloy and its relevant role on the mechanical performance. Highlights: An elasto-viscoplastic thermodynamically consistent constitutive model for diffusion-assisted phase transformations is developed. The model accounts for the chemistry-plasticity coupling occurring at high temperature and the crystal rotations produced by microtwin propagation. The model is implemented in a CP-FEM framework to study the single crystal and polycrystalline creep deformation of Ni-based superalloy MD2. A relation between rotations of the crystal and the creep life of the different crystal orientations is established. The strong anisotropy of microtwin formation plays a crucial role in the asymmetric behavior of the alloy and, therefore, its mechanical performance.